ANALISA PEMANFAATAN CCTV DALAM MENDUKUNG TUGAS POKOK DANUNIT IDIK DI DENPOM IV/2 YOGYAKARTA - Siregar, Paulina; Bremi, Rayhan Ontosena; Kurniatun, Endang Sri; Hartini, Sri (PPM Sdirjianbang Akademi Militer, 2025)
Currently, CCTV technology is becoming the center of attention from various circles, especially in the judicial world. This is because the application of CCTV technology with artificial intelligence can make a significant contribution to criminal investigation tasks by facilitating the collection of stronger evidence and the identification of criminals, although there are still challenges related to the limitations of the existence and validity of evidence in court. However, the fact is that the legality of CCTV as valid evidence has not yet been established as legitimate proof in court. Nevertheless, CCTV has greatly supported the tasks of the Criminal Investigation Unit at the Military Police Detachment IV/2 Yogyakarta. This research aims to understand how the Criminal Investigation Unit utilizes CCTV in its primary duties. This research employs a descriptive qualitative approach with direct observation by the researcher as an instrument. The researcher also conducted interviews and searched for documents that could strengthen the findings. The data was then analyzed in-depth and holistically regarding the phenomenon being studied, along with a deeper contextual understanding. The results of the research indicate that the use of CCTV greatly supports the primary duties of investigation unit commander at the Military Police Detachment IV/2 Yogyakarta. The results from CCTV can enhance the performance of investigators in uncovering cases. CCTV results also provide accurate information in the investigation process, allowing investigative activities to proceed more effectively and efficiently.